Desempenho da colhedora de milho Penha CLM-350: parte III - danos mecânicos - Furlani Jr, J.A. [UNESP]; Guimarães Jr, J.B.; Balastreire, L.A. (Universidade de São Paulo (USP), Escola Superior de Agricultura, 1977)
Cm vistas a estudar o efeito do sistema de debulhamento na qualidade dos grãos de milho, realizou-se o presente trabalho, onde foram estudados os danos mecânicos sofridos pelos grãos, bem como os danos mecânicos invisíveis, evidenciados pelos testes de germinação. Nos diversos tratamentos estudados, determinou-se a porcentagem de umidade presente nos grãos de milho. Definiu-se a velocidade periférica do debulhador, pelo diâmetro (300 mm) do mesmo e as rotações, para os diversos tratamentos. O delineamento experimental foi de blocos ao acaso com 5 tratamentos e 6 repetições onde foram estudados os valores percentuais de grãos inteiros e quebrados, os teores de umidade correspondentes e os valores de germinação através da análise de variância. Empregou-se o teste F aos níveis de 1% e 5% de probabilidade e o teste Tukey para comparação entre as médias. da análise pode-se concluir que em relação ao teor de umidade dos grãos, os tratamentos não diferiram estatisticamente.

This work deals with the effect of the shelling system of a corn harvester on the quality of corn kernels. The mechanical damage, both visible and invisible were evaluated, the last one using germination tests. The moisture content of the kernels for each treatment was determined. The peripheral velocity of the shelling cylinder was defined considering the diameter (300 mm) and the angular velocity for the various treatments. The statistical design used was randomized blocks with 5 treatments and 6 repetitions to study the percentage values of whole and broken kernels, the correspondent moisture content and germination values. The F test at 1% and 5% probability level and Tukey's test were used for comparison between means. From the analysis it is possible to conclude that the effect of moisture content was not statistically significant with an average moisture content of 15,78%. The comparions between means showed that there are highly significant differences for the peripheral velocity of the shelling cylinder on the percentage of whole kernels, it could be assumed that there was an inverse relation between those two parameters for the conditions tested. The germination test which was used to characterize invisible damage showed significant differences for some of the treatments. The results indicated an inverse relation between peripheral velocity of the shelling cylinder and the percentage of germination of the whole kernels. Some influence of the material flow through the shelling system was detected suggesting further studies of this phenomenon if these harvesters are to be used to harvest corn seed.
Performance of the Penha CLM-350 corn harvester: part III - mechanical damage